Surgical repair of tricuspid valve leaflet tear following percutaneous closure of perimembranous ventricular septal defect using Amplatzer duct occluder I: Report of two cases - Saatchi Mahesh Kuwelker; Devi Prasad Shetty; Bharat Dalvi (Wolters Kluwer Medknow Publications, 2017)
Tricuspid valve (TV) injury following transcatheter closure of perimembranous ventricular septal defect (PMVSD) with Amplatzer ductal occluder I (ADO I), requiring surgical repair, is rare. We report two cases of TV tear involving the anterior and septal leaflets following PMVSD closure using ADO I. In both the patients, the subvalvular apparatus remained unaffected. The patients presented with severe tricuspid regurgitation (TR) 6 weeks and 3 months following the device closure. They underwent surgical repair with patch augmentation of the TV leaflets. Postoperatively, both are asymptomatic with a mild residual TR.